Thirteen-Year Follow-Up of a Patient with Liver Cirrhosis Resulting from the Overlap Syndrome of Autoimmune Hepatitis and Primary Biliary Cholangitis: Severe COVID-19 and Liver Transplantation - A. Kh. Odintsova; D. R. Akberova; L. R. Sadykova; N. A. Cheremina; M. M. Minnullin; A. A. Kirshin; E. N. Gabitova; A. Yu. Khasanshina; D. I. Abdulganieva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
Aim: to present the difficulties of long-term management of a patient with liver cirrhosis in the outcome of overlap syndrome (autoimmune hepatitis and primary biliary cholangitis) who suffered from severe COVID-19 infection.Key points. The diagnosis of liver cirrhosis as an outcome of overlap syndrome (autoimmune hepatitis and primary biliary cholangitis) was established at the patient’s age of 33 years. At the age of 40, the patient became pregnant for the first time, the pregnancy proceeded well, and a cesarean section was performed at 36 weeks. At the age of 45, the patient suffered a severe new coronavirus infection, followed by decompensation of liver cirrhosis, which required liver transplantation 4 months after COVID-19, followed by a favorable postoperative course.Conclusion. This clinical case demonstrates the successful onset and outcome of pregnancy in a patient with liver cirrhosis in the outcome of overlap syndrome (autoimmune hepatitis and primary biliary cholangitis). The pronounced activity of the disease after severe new coronavirus infection required liver transplantation with successful outcome.